The Labor Analgesia Requirements in Nulliparous Women Randomized to Epidural Catheter Placement in a High or Low Intervertebral Space. (December 2017) - Moore, Albert; Villeneuve, Valerie; Bravim, Bruno; el-Bahrawy, Aly; el-Mouallem, Eva; Kaufman, Ian; Hatzakorzian, Roupen; Li Pi Shan, William
Abstract : BACKGROUND: We hypothesized that an epidural catheter placed in a lower vertebral interspace will require less medication for labor analgesia. METHODS: Nulliparous women requesting neuraxial labor analgesia were randomized to epidural catheter placement at the ultrasound-confirmed L1-2 or L4-5 interspace. Patient-controlled epidural analgesia and breakthrough manual epidural boluses of 10 mL of 0.125% bupivacaine with 50 µg of fentanyl or 8 mL of 2% lidocaine were utilized. Abdominal and perineal pain scores were assessed at 30 and 60 minutes after standardized initiation of epidural analgesia. Pain scores during pushing were assessed after delivery. The primary outcome was the proportion of patients requiring manual boluses and was compared using a χ 2 test. Secondarily, we analyzed the number of boluses given in early (up to 4 hours before delivery) versus late labor using χ 2 tests and the pain scores using Mann-Whitney U tests, with adjustment of P values for multiple testing. RESULTS: We analyzed 148 patients. Overall, the percentage of patients in the low versus high groups who required manual boluses was 46% vs 51% ( P = 1.0). For the 56 patients in each group who delivered vaginally, 22 (52%) vs 20 (48%) manual boluses were given to the low epidural group in early versus late labor, compared to 9 (20%) vs 36 (80%) in the high epidural group ( P = .014). There was no statistical difference in patient-controlled epidural analgesia requirements or patient satisfaction. Comparing the low versus high groups, the median (interquartile range) pain scores were: 3 (1, 6) vs 0 (0, 2) ( P = .013) at 30 minutes and 1 (1, 3) vs 0 (0, 1) ( P = .013) at 60 minutes for abdominal pain; 0 (0, 2) vs 1 (1, 3) ( P = .36) and 0 (0, 1) vs 1 (1, 3) ( P = .014) at these same time points for perineal pain; and 1 (0, 5) vs 0 (0, 3) ( P = .9) for abdominal and 2 (0, 5) vs 4 (1, 8) ( P = .025) for perineal pain during pushing. The percentage of patients who underwent instrumental delivery was 15% vs 5% ( P = .06) for the low versus high group. CONCLUSIONS: An L4-5 epidural catheter initially provides less relief of abdominal pain but more relief of perineal labor pain. Patients with an L4-5 catheter require more manual boluses during early labor but less during late labor. The possible association of low epidural catheters with instrumental delivery merits further investigation. Abstract : Published ahead of print May 11, 2017.